Cycloprodigiosin: A multispecies settlement cue for scleractinian coral larvae - Laura J. Fiegel; Samuel Nietzer; David Brefeld; Robbert C. Geertsma; Ronald Osinga; Peter J. Schupp; Matthias Y. Kellermann (Scientific Reports)
Abstract The survival of coral reefs depends on the rejuvenation of coral populations with the potential to adapt and survive a changing climate. Assisted sexual reproduction has become an important tool in reef management. One bottleneck is the efficient and manageable induction of coral larval settlement. Here we report cycloprodigiosin (CYPRO) as a multispecies cue which induces complete larval settlement at rates between 40 and 93% in four brooding and five broadcast spawning species. All nine tested species showed similar uptake and conversion of CYPRO (photolytic degradation), which together initiate and complete the transition to successful settlement. Due to its chemical stability and low water solubility, the component can be easily stored, transported and applied on clean substrates, which might increase the chances of survival of the settled recruits. Thus, this broad settlement cue has the chance to advance reef restoration projects.